2017
DOI: 10.1111/anae.14082
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic ultrasound‐guided short‐axis needle tip navigation technique vs. landmark technique for difficult saphenous vein access in children: a randomised study

Abstract: Dynamic ultrasound-guided short-axis needle tip navigation is a novel technique for vascular access. After venipuncture, the needle and catheter are further advanced within the vessel lumen under real-time ultrasound guidance with constant visualisation of the needle tip in the short-axis view. This can minimise the risk of transfixing the cannulated vessel. We compared two techniques for non-visible saphenous vein cannulation under general anaesthesia in children weighing ≥ 3 kg and less than four years of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 18 publications
1
65
0
2
Order By: Relevance
“…The choice of suitable veins and puncture methods is the critical point to facilitate peripheral IV placement. In addition to its shallow position, the saphenous vein may offer other features such as the greater vessel diameter and relatively xed location, which would make it a desirable option for IV placement for infants and toddlers [14]. Riera et al [9] recommended saphenous veins as a superior rst choice for IV cannulation in smaller children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of suitable veins and puncture methods is the critical point to facilitate peripheral IV placement. In addition to its shallow position, the saphenous vein may offer other features such as the greater vessel diameter and relatively xed location, which would make it a desirable option for IV placement for infants and toddlers [14]. Riera et al [9] recommended saphenous veins as a superior rst choice for IV cannulation in smaller children.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size required was calculated on the basis of the success rate of the rst attempt. The previous study reported rst-attempt success rates of about 51% with the conventional method for saphenous venous cannulation [14]. We assumed that a 30% increase in the success rate of the rst attempt using the ultrasound technique should be signi cantly different compared with the traditional anatomic landmark approach.…”
Section: Statistical Analysis and Sample Size Calculationmentioning
confidence: 99%
“…In one tertiary academic pediatric institution, the entire procedure, including preparation and securing of the catheter, took an average of 2‐3 minutes in children with known features of DiVA . Similarly, higher first attempt success rates and a greater success of cannulation within 10 minutes were seen with US‐guided PIV cannulation attempted at the greater saphenous vein in children with DiVA compared with the landmark technique . Within the intensive care unit (ICU), US‐guided PIV placement facilitated subsequent peripheral inserted central catheter (PICC) placement with an 85% first attempt success rate, 95% overall success rate and 113 second total time to cannulation in children under 5 years of age .…”
Section: Search Methodologymentioning
confidence: 99%
“…These children were known to have had several failed PICC line attempts by experienced neonatal ICU nurses prior to the IR attempts . Despite a limited number of studies, the positive outcomes reported with US‐guided PIV placement under deep sedation or general anesthesia is encouraging …”
Section: Search Methodologymentioning
confidence: 99%
See 1 more Smart Citation